2016
DOI: 10.3109/14397595.2016.1162261
|View full text |Cite
|
Sign up to set email alerts
|

Biologic therapy in familial Mediterranean fever

Abstract: Familial Mediterranean fever (FMF) is the most common autoinflammatory hereditary disease characterized by self-limited attacks of fever and serositis. Although colchicine is the gold standard treatment for the attacks ∼10% of cases of FMF are resistant or intolerant to effective doses of colchicine. In such cases, however, there are increasing numbers of case reports or clinical trials treated by biologic agents which directly target the proinflammatory cytokines. Anti-interleukin-1 (IL-1) treatment has prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 56 publications
0
20
0
2
Order By: Relevance
“…However, none of these studies were RCTs. In one review, Koga et al reported that 29 FMF patients in various studies had successful results with anti-TNF agents [16]. The efficacy of anti-TNF drugs in the treatment of colchicine-resistant FMF is not yet clear.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of these studies were RCTs. In one review, Koga et al reported that 29 FMF patients in various studies had successful results with anti-TNF agents [16]. The efficacy of anti-TNF drugs in the treatment of colchicine-resistant FMF is not yet clear.…”
Section: Discussionmentioning
confidence: 99%
“…Colchicine is currently being used confidently in several diseases due to its anti-inflammatory effect. [31][32] In a recent experimental study which investigated the effects of colchicine, a microtubule-disrupting agent, on skeletal muscle ischemic injury in rats, the authors suggested that 1mg/kg colchicine significantly decreased levels of malondialdehyde, TNF-α, and IL-1β and increased superoxide dismutase in ischemic tissues. 33 In addition, at higher doses colchicine exerts various other inflammatory effects including suppression of phospholipase A2 activation, lysosomal enzyme release, and phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Chronische destruktive (Hüft-)Arthritiden [86,87] sowie HLA-B27-negative seronegative Spondyloarthritis [88,89] sind als gesondert zu betrachtende Manifestationen des FMF anzusehen, die sich häufig durch Colchicin nicht ausreichend therapieren lassen. In diesen Fällen kann der Einsatz von nichtsteroidalen Antiphlogistika (NSAR), lokalen Glukokortikoiden, Methotrexat oder auch TNF-Blockern sinnvoll sein [3,90]. Kontrollierte Studien liegen hierzu aber nicht vor.…”
Section: Therapieempfehlungunclassified